2006
DOI: 10.1637/7273-090704r1.1
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Effect of a Naturally Occurring Mutation in Glycoprotein L on Marek's Disease Virus Pathogenesis

Abstract: We recently reported a comparison of glycoprotein-encoding genes of different Marek's disease virus pathotypes (MDVs). One mutation found predominantly in very virulent (vv)+MDVs was a 12-bp (four-amino acid) deletion in the glycoprotein L (gL)-encoding gene in four of 23 MDV strains examined (three were vv+MDVs and one was a vvMDV). This mutation was noted in the gL of the TK (615K) strain, but not in the RL (615J) strain of MDV. These strains have identical mutations in the meq gene characteristic of vv+MDVs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The deletion in MDV013/MDV013.5 was also found in some highly virulent strains [15]. However, this deletion does not seem to be correlated with increased virulence [48]. The Chinese and European strains showed a deletion in the same region of MDV056.…”
Section: Discussionmentioning
confidence: 93%
“…The deletion in MDV013/MDV013.5 was also found in some highly virulent strains [15]. However, this deletion does not seem to be correlated with increased virulence [48]. The Chinese and European strains showed a deletion in the same region of MDV056.…”
Section: Discussionmentioning
confidence: 93%
“…As mentioned previously, gL has been proposed as important factor to virus entry and cell-tocell spread via hetero-oligomeric complex formation with gH. However, there is an association between MDV virulence and naturally occurring gL mutation in MDV strains of varying virulence [26]. Furthermore, while not the primary goal of this study, the cell surface expression of MHC class II in CEF infected with mutant MDVs infected was monitored.…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have been conducted to identify molecular markers that could be used to pathotype MDVs and that will aid in understanding the molecular bases of MDV increased virulence (Lupiani et al, 2004;Shamblin et al, 2004;Santin et al, 2006;Spatz & Silva, 2007;Spatz et al, , 2008Tavlarides-Hontz et al, 2009;Spatz, 2010;Renz et al, 2012). However, specific virus-encoded factors of MDV-1 that contribute to enhanced virulence are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular changes in the oncogene meq have been shown to be associated with pathogenicity alteration of MDV-1, but they do not necessarily correlate with the already existing pathotyping system (Lupiani et al, 2004;Shamblin et al, 2004;Spatz & Silva, 2007;Spatz et al, , 2008Spatz, 2010;Renz et al, 2012). Changes in other regions such as glycoprotein L (Santin et al, 2006;Tavlarides-Hontz et al, 2009) and pp38 (Shamblin et al, 2004) have also been associated with increase in virulence, but the correlation with current classification in pathotypes remains elusive. Recently, Morgan et al (2008) reported differential expression of MDV-1 microRNA in MDVs, with higher expression of mdv1-miR-M4 and mdv1-miR-M2 in highly virulent MDVs than in less virulent MDVs.…”
Section: Introductionmentioning
confidence: 99%